Characterization of Arabidopsis thaliana cDNAs that render yeasts tolerant toward the thiol-oxidizing drug diamide. - Kushnir, S (1995)
Diamide oxidizes cellular thiols and induces oxidative stress. To isolate plant genes which may, when overexpressed, increase tolerance of plants toward oxidative damage, an in vivo diamide tolerance screening in yeasts was used. An Arabidopsis cDNA library in a yeast expression vector was used to transform a yeast strain with intact antioxidant defense. Cells from approximately 10(5) primary transformants were selected for resistance to diamide. Three Arabidopsis cDNAs which confer diamide tolerance were isolated. This drug tolerance was specific and no cross tolerance toward hydroperoxides was found. One cDNA (D3) encodes a polypeptide which has an amino-terminal J domain characteristic of a divergent family of DnaJ chaperones. Another (D18) encodes a putative dTDP-D-glucose 4,6-dehydratase. Surprisingly, the third cDNA (D22) encodes a plant homolog of gamma-glutamyltransferases. It would have been difficult to predict that the expression of those genes would lead to an improved survival under conditions of depletion of cellular thiols. Hence, we suggest that this cloning approach may be a useful contribution to the isolation of plant genes that can help to cope with oxidative stress.